First Environmental Investigation of Toxigenic Clostridium difficile at a Large Hospital in Bangladesh. (4th October 2017) - Alam, M Jahangir; Begum, Khurshida; Rashid, Tasnuva; Hasan, Irtiza; McPherson, Jacob; Hossain, Feroz; Miranda, Julie; Garey, Kevin W
Abstract: Background: Toxigenic Clostridium difficile is the most common cause of infectious diarrhea in hospitalized patients in the developed world and an emerging pathogen in developing countries due to increased use of broad-spectrum antibiotics. Although likely ubiquitous worldwide, the prevalence of toxigenic C. difficile spores in the hospital environs of developing countries is poorly understood. The objectives of the study are to isolate and characterize C. difficile from the hospital environs of a large hospitals in Dhaka, Bangladesh. Methods: As part of our environmental surveillance effort, we collected 330 shoe-bottom swab samples from hospital employees, patients, and visitors inside of a large hospital in Dhaka, Bangladesh. Samples were analyzed for C. difficile using anaerobic enrichment culture and molecular methods. Suspected colonies from cycloserine cefoxitin fructose agar (CCFA) plates were identified by PCR ( tcdA, tcdB, cdtA, cdtB and tpi genes) and strain typed using fluorescent PCR ribotyping, and MLVA methods. Results: A total 149 of 333 (44.7%) shoe-bottom swab samples were culture positive for C. difficile of which 19.8% samples were toxigenic ( tcdA and tcdB ) C. difficile. A total of 11 distinct ribotypes were identified from 58 toxigenic C. difficile isolates tested. Predominant ribotypes were F053-163 (24.1%), F017 (20.7%), F106 (19.0%), F014-020 (17.2%). Other ribotypes were R001, F005, F010, F018, F054, F216, and FP407. No R027 and R078 C. difficile isolated. A broad MLVA diversity has been seen among the tested strains. Conclusion: We identified a high prevalence of toxigenic C. difficile with diverse ribotypes from hospital environmental shoe-bottom swabs in Bangladesh. This is the first hospital environmental report of C. difficile from Bangladesh. Disclosures: All authors: No reported disclosures.